Impact of COVID-19 pandemic on people with alcohol use disorder in Kerala– An observation from Thrissur district (Kerala Journal of Psychiatry, 2020)
The novel coronavirus pandemic had caused the closure of beverage outlets in Kerala in late March 2020. There were a few suicides in the immediate period, which were highlighted in the media attributing to non-availability of alcohol. An observational study of patients admitted at the De-addiction Centre, NEST and Jubilee Mission Medical College and Research Institute was done. We recorded our observations from the closure of the beverage outlets until two weeks after. Though the government anticipated at least 100 patients, we encountered only 17. Those admitted were brought in delirium, with seizures or injuries sustained during delirium. The possible reasons behind this disparity are discussed which included the sale of illicit liquor or use of home-made preparations. The current situation arose due to a lack of planning and sudden closure of beverage outlets without warning being issued to mental health professionals. Opinions regarding steps to be taken for similar situations in the future are posited.
Keywords: COVID-19; alcohol use disorder; delirium; withdrawal